Preconcentration of Copper Using 1,5-Diphenyl Carbazide as the Complexing Agent via Dispersive Liquid-Liquid Microextraction and Determination by Flame Atomic Absorption Spectrometry - Reyhaneh Rahnama; Elaheh Shafiei; Mohammad Reza Jamali (Journal of Chemistry)
We report a simple and sensitive microextraction system for the preconcentration and determination of Cu (II) by flame atomic absorption spectrometry (FAAS). Dispersive liquid-liquid microextraction is a modified solvent extraction method and its acceptor-to-donor phase ratio is greatly reduced compared with other methods. In the proposed approach, 1,5-diphenyl carbazide (DPC) was used as a copper ion selective complexing agent. Several variables such as the extraction and dispersive solvent type and volume, pH of sample solution, DPC concentration, extraction time, and ionic strength were studied and optimized for a quantitative preconcentration and determination of copper (II) and at the optimized conditions: 60 μL, 0.5 mL, and 5 mL of extraction solvent (chloroform), disperser solvent (ethanol), and sample volume, respectively, a linear calibration graph was obtained over the concentration range of 10–200 μg L−1 for Cu (II) with R2 = 0.9966. The limit of detection (3Sb/m), and preconcentration factor are 2 μg L−1 and 25, respectively. The relative standard deviation (n=10) at 100 μg L−1 of Cu (II) is 2.5%. The applicability of the developed technique was evaluated by application to spiked environmental water samples.